2011
DOI: 10.1007/s10562-011-0574-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective α-aminoxylation Reactions Catalyzed by Isosteviol-proline Conjugates in Buffered Aqueous Media

Abstract: Chiral amphiphilic conjugate catalysts were designed and synthesized by covalently connecting L-proline with an inexpensive natural product, isosteviol. These catalysts demonstrated remarkable efficiency in the asymmetric a-aminoxylation of aldehydes and ketones using nitrosobenzene in phosphate buffer solution, resulting in good to high yields and excellent enantioselectivities without using any additives. At pH 9.1, the amphiphilic catalysts showed a pH responsive ability in phosphate buffer solution, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The catalyst was utilized to encourage an aldol reaction. Chiral amphiphilic conjugate catalysts were outlined and integrated by covalently linking l -proline with an isosteviol, an aminoxylation of aldehydes, and ketones utilizing nitrosobenzene in phosphate buffer arrangement, bringing about the high level of enantioselectivities [ 176 ]. In another study, isosteviol amino catalyst conjugates as an organo-catalyst for asymmetric three-component Mannich Reactions.…”
Section: Other Miscellaneous Usesmentioning
confidence: 99%
“…The catalyst was utilized to encourage an aldol reaction. Chiral amphiphilic conjugate catalysts were outlined and integrated by covalently linking l -proline with an isosteviol, an aminoxylation of aldehydes, and ketones utilizing nitrosobenzene in phosphate buffer arrangement, bringing about the high level of enantioselectivities [ 176 ]. In another study, isosteviol amino catalyst conjugates as an organo-catalyst for asymmetric three-component Mannich Reactions.…”
Section: Other Miscellaneous Usesmentioning
confidence: 99%
“…Nevertheless, the skeleton structures to construct thiourea catalysts are very limited, and there is still great demand for novel bifunctional thiourea catalysts for this purpose. Recently, we found that, similar to the cinchona alkaloids, the incorporation of a chiral diterpene moiety (isosteviol) into the thiourea catalysts led to impressive results in asymmetric reactions . Inspired by the excellent chiral structural skeleton of isosteviol, we designed and synthesized a new class of primary amine‐thiourea bifunctional catalysts 3a and 3b .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that, similar to the cinchona alkaloids, the incorporation of a chiral diterpene moiety (isosteviol) into the thiourea catalysts led to impressive results in asymmetric reactions. [31][32][33][34][35][36][37] Inspired by the excellent chiral structural skeleton of isosteviol, we designed and synthesized a new class of primary amine-thiourea bifunctional catalysts 3a and 3b. With these novel catalysts in hand, the effects of the thiourea catalysts were investigated.…”
Section: Introductionmentioning
confidence: 99%